Blue Iridium (III) Phosphorescent OLEDs with High Brightness Over 10 000 cd m−2 and Ultralow Efficiency Roll‐Off. Issue 1 (9th November 2022) - Wu, Chengcheng; Wang, Min; Tong, Kai‐Ning; Zhang, Meng; Li, Wansi; Xu, Zhuhua; Zhang, Wei‐Long; Wu, Yuan; Yang, Chen; Fu, Hong‐Yan; Chen, Season Si; Ng, Maggie; et al.
Abstract: Herein, a family of six [3+2+1] coordinated 2‐(2′, 4′‐difluorophenyl) pyridine‐based Iridium(III) complexes with intermolecular interactions have been designed to improve their emission properties. These molecular interactions have been regarded as an effective way to suppress non‐radiative decay and enhance the photoluminescence quantum yield (PLQY) of the light‐emitting materials. Specifically, complex 3 functionalized with new −CF3 ligand exhibits PLQY of up to 100%, and the emission peak at ≈485 nm with short excited‐state lifetime down to 1 µs. Therefore, the blue phosphorescent organic light‐emitting diode (OLED) based on complex 3 dopant exhibits excellent performance with a maximum external quantum efficiency of 22.0% and low efficiency roll‐off. Upon increasing the current density to 250 mA cm −2, high brightness value of 53 400 cd m −2 is achieved, which is not attainable with the similar molecular structure that we have reported recently, indicating the importance of the presence of the (CF···H/CN···H) interactions. Given the well‐overlapping of the emission spectra of these Iridium(III) complexes and absorption spectrum of v ‐DABNA emitter, complex 3 has been successfully applied as a sensitizer for v ‐DABNA‐based OLED, and a maximum current efficiency of 27.13 cd A −1 with high brightness level of up to 10 000 cd m −2 have been achieved. Abstract : Pyridine‐based Ir(III) complexes have been rationally designed to improve their emission brightness. The blue phosphorescent organic light‐emitting diodes based on complex 3 dopant (functionalized with new −CF3 ligand) exhibit excellent performance with a maximum external quantum efficiency of 22.0% and extremely low efficiency roll‐off. Upon increasing the current density to 250 mA cm −2, high brightness value of 53 400 cd m −2 is achieved.